Driving Pressure Influence in Voltage Maps Measurement Process Using Advanced Pneumatic Mapping Probe - Marek Kukucka (Advances in Electrical and Electronic Engineering, 2016)
Our paper deals with the method of the voltage-impedance map measurement process as a method useful for the electric mapping of human skin. The area of research extends from the basic research to its practical application in acupuncture skin mapping and acupuncture point localization and visualization. The problem of sufficient skin coverage and electrical contact with measuring electrodes is solved by the conventional mechanical telescopic electrodes and by the pneumatic matrix electrode probe. A 2D or 3D voltage-impedance map of skin is an output of the measuring, interpretation and evaluation process. New pneumatic construction of measuring probe was implemented to achieve a better coverage of specified skin area and get a reduced force range of the touching electrodes allowing the steady contact of the skin-electrode. A skin contact is related to the driving pressure of touching electrodes. Our paper offers experimentally measured results, voltage maps of skin on specific areas, selected measured and described acupuncture points and their applications in electro-acupuncture.